Sự trải nghiệm và hành vi gắn kết khách hàng – Vai trò của Thuyết bản sắc xã hội: Nghiên cứu thực nghiệm dịch vụ du lịch sức khỏe trong bối cảnh hậu COVID-19 - Vũ Thị Mai , Chi; Trần Hà Minh , Quân (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2022)
The study is based on Social Identity Theory to examine the relationship between customer experience and customer engagement behavior of the wellness tourism service in the post-COVID-19 context. Qualitative and quantitative research methods are combined to carry out the study. The data collected from the survey of 198 tourists was analyzed by Partial Least Squares Structural Modeling (PLS-SEM). Research results show that there is a positive relationship between customer experience and customer engagement behavior through the mediating roles of customer-employee identification and customer-firm identification. From the findings, the study proposes some managerial implications for the wellness tourism service industry in order to design an appropriate customer experience to increase customer engagement behavior in the post-COVID-19 context. In addition, the study suggested some limitations and directions for further research.
Keywords: Customer experience; Customer engagement behavior; Social Identity Theory; Wellness tourism